ON THE RELIABILITY AND MAINTAINABILITY OF INDIVIDUAL ELEMENTS OF GAS DISTRIBUTION SYSTEM VALVES - Palieiev, A.; Kotukh, V. (Municipal economy of cities. Series: «Economy science», 2024)
At the current stage of the development of society, including in our country, there is an accelerating urbanisation process. The increasing role of cities in the country’s development, on the one hand, contributes to social, scientific, and technical development, and on the other hand, creates new economic, ecological, informational, social, and other challenges. One of the features of urbanisation is the increase in energy use. One of the primary sources of energy is natural gas. Transportation of natural gas from deposits and gas storages and its distribution to consumers occurs with the help of gas transportation systems. One of the components of gas transportation systems is gas distribution systems. They have a broad range of components and elements and a long list of requirements for the conditions of their manufacture, operation, and repair, and they are under the influence of numerous external factors. Such multivariability necessitates the development of specific models, methods, and information technologies for monitoring their state in conditions of uncertainty to solve the problems of forecasting and planning repair work on gas transportation systems. During the study, we determined the main factors affecting the reliability of gas pipelines overall. We also analysed the operational characteristics of the shut-off valves of elements of gas distribution systems, typical malfunctions, and the main features of its diagnosis and repair. During operation, gas distribution system elements are under the influence of many factors that affect their reliability. Considering all the factors arising at different stages of the life cycle of the gas distribution system elements will ensure their operational reliability, indestructibility, and durability. The results of the analysis of individual parameters of shut-off fittings of gas distribution systems are applicable for creating models and methods of monitoring, forecasting, and planning repair work on gas transportation systems under conditions of uncertainty.